Oligotrophy as a major driver of mercury bioaccumulation in medium-to high-trophic level consumers: A marine ecosystem-comparative study. (February 2018) - Chouvelon, Tiphaine; Cresson, Pierre; Bouchoucha, Marc; Brach-Papa, Christophe; Bustamante, Paco; Crochet, Sylvette; Marco-Miralles, Françoise; Thomas, Bastien; Knoery, Joël
Abstract: Mercury (Hg) is a global contaminant of environmental concern. Numerous factors influencing its bioaccumulation in marine organisms have already been described at both individual and species levels (e.g., size or age, habitat, trophic level). However, few studies have compared the trophic characteristics of ecosystems to explain underlying mechanisms of differences in Hg bioaccumulation and biomagnification among food webs and systems. The present study aimed at investigating the potential primary role of the trophic status of systems on Hg bioaccumulation and biomagnification in temperate marine food webs, as shown by their medium-to high-trophic level consumers. It used data from samples collected at the shelf-edge (i.e. offshore organisms) in two contrasted ecosystems: the Bay of Biscay in the North-East Atlantic Ocean and the Gulf of Lion in the North-West Mediterranean Sea. Seven species including crustaceans, sharks and teleost fish, previously analysed for their total mercury (T-Hg) concentrations and their stable carbon and nitrogen isotope compositions, were considered for a meta-analysis. In addition, methylated mercury forms (or methyl-mercury, Me-Hg) were analysed. Mediterranean organisms presented systematically lower sizes than Atlantic ones, and lower δ 13 C and δ 15 N values, the latter values especially highlighting the more oligotrophic character of Mediterranean waters. Mediterranean individuals also showed significantly higher T-Hg and Me-Hg concentrations. Conversely, Me-Hg/T-Hg ratios were higher than 85% for all species, and quite similar between systems. Finally, the biomagnification power of Hg was different between systems when considering T-Hg, but not when considering Me-Hg, and was not different between the Hg forms within a given system. Overall, the different parameters showed the crucial role of the low primary productivity and its effects rippling through the compared ecosystems in the higher Hg bioaccumulation seen in organisms from oligotrophic Mediterranean waters. Graphical abstract: Image 1 Highlights: Seven offshore species from the Mediterranean Sea and the Atlantic Ocean examined. Individual sizes, δ 13 C and δ 15 N values, Hg concentrations and speciation compared. Mediterranean and Atlantic organisms differed for most of the parameters studied. δ 15 N values reflected the different trophic status at the base of the two systems. Oligotrophy likely drives the higher Hg bioaccumulation by Mediterranean organisms. Abstract : Higher Hg bioaccumulation by Mediterranean organisms likely linked to the lower primary productivity (oligotrophy) of Mediterranean waters in comparison with Atlantic waters.